2009
DOI: 10.1007/s12020-009-9274-z
|View full text |Cite
|
Sign up to set email alerts
|

Central leptin versus ghrelin: effects on bone marrow adiposity and gene expression

Abstract: This study compared the central effects of ghrelin and leptin on body and bone marrow adiposity and gene expression in adipose tissue and bone marrow. Male Sprague-Dawley rats were injected intracerebroventricular (ICV) twice daily with control, 66 ng ghrelin (G66), 330 ng ghrelin (G330), or 5 μg leptin (L5) for 5 days. Food intake (FI) and body weight (BW) were measured daily. Gene expression in adipose tissue and bone marrow was assessed using RT-PCR. Leptin reduced FI (P < 0.05) and BW (P < 0.05), whereas g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
1
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 28 publications
0
18
1
2
Order By: Relevance
“…Hypothalamic leptin administration resulted in rapid (within 4-5 days) decreases in peripheral fat as well as bone marrow fat in ob/ob mice (91,92). In the present study, we observed a dramatic decrease in bone marrow adiposity at 5 weeks post-vector administration but this was associated with the surgery; no significant leptin-specific effect was noted.…”
Section: Resultsmentioning
confidence: 99%
“…Hypothalamic leptin administration resulted in rapid (within 4-5 days) decreases in peripheral fat as well as bone marrow fat in ob/ob mice (91,92). In the present study, we observed a dramatic decrease in bone marrow adiposity at 5 weeks post-vector administration but this was associated with the surgery; no significant leptin-specific effect was noted.…”
Section: Resultsmentioning
confidence: 99%
“…Here, it would be important to ensure that such leptin supplementation does not increase circulating leptin to supraphysiological concentrations. Indeed, exogenous leptin administration also leads to profound MAT loss in animals that are not leptin deficient (34,82,83). In such states of leptin sufficiency, effects of exogenous leptin typically depend upon administration of high doses that elevate circulating leptin to supraphysiological concentrations (84).…”
Section: Endocrine Factors As Potential Mediators Of Crassociated Matmentioning
confidence: 99%
“…The duration of ICV ghrelin treatment (21 days) in this study could be considered relatively short to induce profound changes in bone mass. However, it should be noted that establishment of an animal model of chronic ICV treatment is technically challenging and the present study is the longest ICV ghrelin treatment attempted (21 days), with previous studies infusing ghrelin for only 6–12 days [8][10], [12]. Future study using Alzet osmotic pump model 2ML4 could extend chronic infusion up to 28 days.…”
Section: Discussionmentioning
confidence: 90%
“…Chronic ICV ghrelin infusion increased food intake and weight gain [8], reversed the effect of leptin on food intake [9], increased the glucose utilization rate of adipose tissue [10], and increased lipogenic enzymatic activity in adipose tissue and liver [11]. A recent study investigated the central effects of ghrelin and leptin on body and bone marrow adiposity, as well as adipose tissue and bone marrow gene expression, and reported central ghrelin had no effect on bone marrow adiposity [12]. However, to date, no study has investigated the effect of chronic ICV ghrelin on bone metabolism.…”
Section: Introductionmentioning
confidence: 99%